Electrochemical kinetics of gold electrodes in SCN−/dimethylsulfoxide solutions - Martins, María Elisa (1978)
The electrochemical behaviour of the Au/SCN− (DMSO) interface is studied at 25°C≤T≤65°C, by means of the triangular potential sweep technique and the RDE. Within a relatively limited potential range the main electrode process is: 3 SCN−=(SCN)3−+2e The kinetics of this reaction involves a mixed control. At higher potentials the electrodissolution of the base metal takes place. Side reactions occurring there make the overall process rather complex. The electrochemical behaviours of the Au/SCN− (DMSO) and Au/SCN− (ACN) are compared.